Analisis Makna dan Fungsi Lagu Mbaba Kampil karya Djaga Depari pada Pernikahan Adat Suku Karo - Ocha Nggelemita Br Tarigan; Amnur Rifai Dewirsyah (Medan Resource Center, 2023)
This study aims to reveal how the meaning and function of the song mbaba kampil by Djaga Depari in traditional Karo weddings. This song has certain characteristics that are different from other songs, making researchers want to reveal the meaning and function of the song mbaba kampil by Djaga Depari at a traditional Karo wedding. This study uses a qualitative descriptive method, the subjects in this study are the people who support the mbaba kampil song, while the object of research is the meaning and function of the mbaba kampil kampil song in the Karo tribe’s traditional wedding. Data collection techniques used are interviews, and documentation. The qualitative data analysis technique uses data reduction, data presentation, and drawing conclusions. The results showed that the song mbaba kampil has a unique lyric and has a deep meaning about the traditional marriage of the Karo tribe. Researchers divide into connotative meaning and denotative meaning. The connotative meaning of the song contains advice, invitation, and information. The denotative meaning of the song takes the words of the Karo tribes cloth and calls commonly used in the Karo tribe, for example, the words tudung, bulang-bulang, kalimbubu. The song also has certain functions, the researcher reveals severel function of the song, namely : (1) as a form of entertainment, (2) functions of traditional ceremonies, (3) functions of family norms, (4) functions of customary norms, (5) functions of advice.